1991
DOI: 10.1002/cne.903140407
|View full text |Cite
|
Sign up to set email alerts
|

An immunocytochemical analysis of the lateral geniculate complex in the pigeon (Columba livia)

Abstract: The lateral geniculate complex (GL) of pigeons was investigated with respect to its immunohistochemical characteristics, retinal afferents, and the putative transmitters/modulators of its neurons. The distributions of serotonin-, choline acetyltransferase-, glutamic acid decarboxylase-, tyrosine hydroxylase-, neuropeptide Y- (NPY), substance P- (SP), neurotensin- (NT), cholecystokinin- (CCK), and leucine-enkephalin- (L-ENK) like immunoreactive perikarya and fibers were mapped. Retinal projections were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 124 publications
6
51
0
1
Order By: Relevance
“…The relatively highest density was detected in the ventral part of the lateral geniculate nucleus (Glv), which receives a strong serotonergic innervation, though to a lesser extent than PT (Cozzi et al, 1991;Challet et al, 1996). Furthermore, the Glv receives direct input from the retina and afferents from the visual Wulst, has reciprocal connections with the optic tectum, and projects to the pretectal nuclei (Guiloff et al, 1987;Güntürkün and Karten, 1991). Lesions of the Glv had shown that this area is involved in visuomotor function (Guiloff et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively highest density was detected in the ventral part of the lateral geniculate nucleus (Glv), which receives a strong serotonergic innervation, though to a lesser extent than PT (Cozzi et al, 1991;Challet et al, 1996). Furthermore, the Glv receives direct input from the retina and afferents from the visual Wulst, has reciprocal connections with the optic tectum, and projects to the pretectal nuclei (Guiloff et al, 1987;Güntürkün and Karten, 1991). Lesions of the Glv had shown that this area is involved in visuomotor function (Guiloff et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…This arrangement could be a powerful cellular mechanism to create illusory motions with the opposite direction to the previous stimulus. Since the nLM projects via the visual thalamus to the forebrain [23,24,51], it is possible that the MAE is integrated at telencephalic level to guide goal-directed behavior as analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the nRt lacks both muscarinic and nicotinic cholinergic receptors [Dietl et al, 1988a;Watson et al, 1988;Güntürkün and Karten, 1991; Bagnoli et al, 1992]. However, this nucleus has an apparently homogenous distribution of γ-aminobutyric acid (GABA)-like terminals, which may stem from the GABAergic neurons of the subpretectal and ventral…”
Section: Introductionmentioning
confidence: 99%
“…It also receives input from the contralateral OT [Hunt and Künzle, 1976;Bischof and Niemann, 1990; Güntürkün et al, 1993;Ngo et al, 1994;Mpodozis et al, 1996]. Electrophysiological studies have shown that this nucleus is involved in the analysis of geometric pattern, brightness, color, and fine spatial detail [Hodos and Karten, 1966;Macko and Hodos, 1984] and is organized into several functionally distinct subdivisions for processing different types of visual information such as color, luminance and Z-axis motion [Wang and Frost, 1992;Wang et al, 1993].Histochemically, the nRt subdivisions stain differentially for acetylcholinesterase (AChE) [Martinez-de-la-Torre et al, 1990] but fail to label for choline acetyltransferase (ChAT) [Güntürkün and Karten, 1991]. It appears that the nRt lacks both muscarinic and nicotinic cholinergic receptors [Dietl et al, 1988a;Watson et al, 1988;Güntürkün and Karten, 1991; Bagnoli et al, 1992].…”
mentioning
confidence: 99%